RETRACTED: Tolerant Movement from Below: Grassroot Agency for Religious Moderation in Indonesian Socio-Political Contexts - Khoiruddin Zuhri, Mishbah; Maulana , Moch. Dimas; Mufti, Muhammad (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2023)
Retracted following a rigorous, carefully concerns considered in the review of the article published in At-Tafkir: Jurnal Pendidikan, Hukum dan Sosial Keagamaan entitled â€œTolerant Movement from Below: Grassroot Agency for Religious Moderation in Indonesian Socio-Political Contextsâ€ Vol. 16, No. 2, May-November 2023, DOI: https://doi.org/10.32505/at.v16i2.9139. The article We Declare Retracted From At-Tafkir: Jurnal Pendidikan, Hukum dan Sosial Keagamaan was then removed at the author's request.. The document and its content have been removed from At-Tafkir: Jurnal Pendidikan, Hukum dan Sosial Keagamaan, and reasonable effort should be made to remove all references to this article.